Estimation of π and σ band contributions in the normal state electrical conductivity of (Bi, Pb)-2223 added MgB2 superconductors. (June 2015) - Tripathi, D.; Dey, T.K.
Highlights: Electrical resistivity of (Bi, Pb)-2223 added MgB2 has been investigated. Electron–phonon coupling constant ( λ ) of MgB2 is unaffected with 2223 addition. Individual contribution of σ and π bands have been estimated. Major electrical conduction takes place through σ band. Abstract: Temperature dependence of the normal state electrical resistivity of polycrystalline MgB2 added with 0, 0.5, 1, 3 and 5 wt. % of (Bi, Pb)-2223 (Bi1.8 Pb0.26 Sr2 Ca2 Cu3 O10+ x ) superconducting powder have been investigated in the light of two band approach based on π and σ bands of MgB2 superconductor. The scattering rates ( γσ, γπ ) and residual resistivity ( ρ 0 σ, ρ 0 π ) of each band are estimated for the investigated samples. Our observation for pure MgB2 shows much higher scattering rate in π bands, as compared to σ bands and hence indicates 'dirty' nature of the samples. However, the addition of 2223 in MgB2 is found to enhance the scattering rate in both bands, but the enhancement is more pronounced in π bands as compared to σ bands. Contribution of each individual band towards the total electrical conductivity of 2223 added MgB2 pellets are separated. Our analysis confirms that σ band contribution shows a small increase with 2223 addition and reaches nearly 89% for 5 wt. % 2223 added MgB2 polycrystalline pellets. The electron–phonon coupling constant ( λ ) of pure and 2223 added MgB2 pellets calculated using Mc-Millan expression is found to be nearly invariant with 2223 addition.